Spleen Stiffness Differentiates Between Acute and Chronic Liver Damage and Predicts Hepatic Decompensation. Issue 6 (July 2019) - Meister, Phil; Dechêne, Alexander; Büchter, Matthias; Kälsch, Julia; Gerken, Guido; Canbay, Ali; Jochum, Christoph
Abstract : Objectives: Spleen stiffness (SS) correlates with liver stiffness (LS) and hepatic venous pressure gradient. The latter is currently the most accurate predictor of hepatic decompensation. Our study aims to check whether SS has a similar predictive capability, while being an easy-to-perform noninvasive test in a real-life patient cohort. Methods: Concomitantly, 210 successive patients were examined and received liver and SS measurements and a standard laboratory. Patients were observed for 1 year in terms of clinical signs of decompensation. Results: One hundred fifty-nine of the initial 210 patients had a valid LS and SS measurement and were evaluable for clinical follow-up. Twelve patients developed a hepatic decompensation; with a SS >39 kPa ( P =0.0005). Especially in a group with elevated LS, patients with a high risk of decompensation could be identified using SS. Patients with comparable LS who suffered from acute liver damage had significantly lower SS than respective patients with chronic liver damage (30.97 vs. 46.03 kPa; P =0.04). Acute liver failure was associated with elevated LS (16.47 kPa) but not with elevated SS (30.97 kPa). Conclusions: The risk of a hepatic decompensation can easily be assessed using SS measurement. Therefore SS measurement might be a powerful screening tool identifying patients who need closer monitoring. Moreover, SS is able to differentiate between acute and chronic or acute on chronic liver damage. Abstract : Supplemental Digital Content is available in the text.